Impact of Surgical Margin Width on Recurrence and Overall Survival Following R0 Hepatic Resection of Colorectal Metastases: A Systematic Review and Meta-analysis. Issue 6 (June 2018) - Margonis, Georgios A.; Sergentanis, Theodoros N.; Ntanasis-Stathopoulos, Ioannis; Andreatos, Nikolaos; Tzanninis, Ioannis-Georgios; Sasaki, Kazunari; Psaltopoulou, Theodora; Wang, Jaeyun; Buettner, Stefan; Papalois, Αpostolos E.; He, Jin; Wolfgang, Christopher L.; et al.
Abstract : Objective: To examine the impact of surgical margin width on survival following R0 hepatic resection for colorectal metastases (CRLM). Summary of Background Data: Although negative resection margin is considered of paramount importance for the prognosis of patients with colorectal liver metastases, optimal resection margin width remains controversial. Methods: Eligible studies examining the association between margin status after R0 hepatic resection for CRLM and survival, including overall survival (OS) and disease-free survival (DFS) were sought using the Medline, Cochrane, and EMBASE databases. Random-effects models were used for the calculation of pooled relative risks (RRs) with their 95% confidence intervals (95% CIs). Results: Thirty-four studies were deemed eligible for inclusion representing a cohort of 11, 147 hepatic resections. Wider resection margin (>1 vs <1 cm) was significantly associated with improved OS at 3 years (pooled RR = 0.86, 95% CI: 0.79–0.95), 5 years (pooled RR = 0.91, 95% CI: 0.85–0.97), and 10 years (pooled RR = 0.94, 95% CI: 0.88–1.00). Similarly, DFS was positively associated with >1 cm resection margin at 3, 5, and 10 years. Interestingly, >1 mm (vs <1 mm) resection margin was significantly associated with improved OS at all-time points. Meta-regression analyses did not reveal any significant modifying role of the study features under investigation, such as the administration of neoadjuvant/adjuvant therapy. Conclusions: Importantly, our findings suggest that while a >1 mm margin is associated with better prognosis than a submillimeter margin, achieving a margin >1 cm may result in even better oncologic outcomes and should be considered if possible. Abstract : Supplemental Digital Content is available in the text